On some remains of dog (Canis familiaris) from the Mesolithic shell-middens of Muge, Portugal - Detry, Cleia (2017)
The dog has a unique relationship with humans. This is demonstrated by the number of breeds that exist today and the important role that dogs play in human society. The archaeological record also shows that this relationship began long ago when groups of hunteregatherers domesticated the wolf probably in several parts of the globe. The dog was domesticated since at least the beginning of the Holocene some 12,000 years ago. It was also, probably, the first species to be domesticated and for reasons completely different from the other species like sheep, goat, pig and cattle e the so-called ‘food animals’ e domesticated later. The identification of a hitherto unpublished Canis skeleton in the Geological Museum of Lisbon, Portugal, 10 years ago, originally recovered from excavations of the Muge shell-middens in 1880, provides new information about the history of early dogs here in the Iberian Peninsula. These remains are dated to the beginning of the Holocene (circa 8000 years BP). The bones were measured and their measurements were compared with those of recent wolf skeletons from Portugal demonstrating that they were significantly smaller than wolf e strong evidence for their domestic status. The Muge dog corroborates the record now coming to light from Mesolithic settlements in other parts of Europe and the Near East dated to the first half of the Holocene. We hope with this article to help complete the picture of the origin and distribution of domestic dog in antiquity.